(untitled) (Iranian Journal of Kidney Diseases, 2022)
Introduction. Bartter syndrome (BS) is a salt losing tubulopathy due to impairment of the transport mechanisms at the thick ascending limb of the Henle’s loop. The aim of this study was to report the clinical course of patients with BS. Methods. Patients with BS were followed from 1996 to 2020 and enrolled to a systematic protocol to confirm primary BS by evaluating the metabolic derangements, nephrolithiasis and nephrocalcinosis. Treatment was based on standard guidelines. Comparisons were made between data at baseline and at the last visit. Results. A total of 13 patients (7 males) with primary BS were analyzed. Two patients had a mutation of the KCNJ1 gene. Age at diagnosis was 3 ± 4.5 years and the follow-up period was 11.19 ± 6.76 years. Metabolic alkalosis was initially detected in 76.92% and remained stable at the last visit (P > .05). Hypokalemia was present in 61.5% of patients at diagnosis, but sustained in 38.46% at the last visit (P < .05). Urine calcium level was 13.3 ± 9.6 mg/ kg/d at the first visit, and significantly reduced to 3.7 ± 2.0 mg/ kg/d at the last visit (P < .05). Nephrocalcinosis was detected by first kidney ultrasonography in 53.8% of patients. Kidney function was preserved, with a glomerular filtration rate of 120.1 ± 28.7 mL/min/ 1.73m2 at last visit. Growth was completely recovered in 71.42% and partially improved in 14.28% of patients after treatment, respectively. All patients received indomethacin and potassium chloride salts. Conclusions. Long-term follow-up of this cohort of BS showed favorable outcomes after treatment resulting in metabolic normalization and growth catch-up in most patients. DOI: 10.52547/ijkd.6657